2017
DOI: 10.1177/2192568217735507
|View full text |Cite
|
Sign up to set email alerts
|

Low-Density Pedicle Screw Constructs for Adolescent Idiopathic Scoliosis: Evaluation of Effectiveness and Cost

Abstract: Study Design:Retrospective cohort study.Objective:To determine whether a low-density (LD) screw construct can achieve curve correction similar to a high-density (HD) construct in adolescent scoliosis.Methods:Patients treated operatively for idiopathic scoliosis between 2007 and 2011 were identified through a database review. A consistent LD screw construct was used. Radiographic assessment included percent correction of major and fractional lumbar curves, T5-T12 kyphosis, and angle of lowest instrumented verte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 17 publications
(41 reference statements)
4
7
0
Order By: Relevance
“…In the present study, we achieved 67% correction in coronal plane with a primary curve flexibility of 41% and an implant density of 68%. Our results are comparable to studies conducted by Morr et al [ 17 ] and Tannous et al [ 18 ], in which they reported 66.6% and 66.9% improvements in the primary curve, respectively. In comparison to Davis [ 7 ], we achieved better coronal correction attributable to increased implant density in the present study.…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, we achieved 67% correction in coronal plane with a primary curve flexibility of 41% and an implant density of 68%. Our results are comparable to studies conducted by Morr et al [ 17 ] and Tannous et al [ 18 ], in which they reported 66.6% and 66.9% improvements in the primary curve, respectively. In comparison to Davis [ 7 ], we achieved better coronal correction attributable to increased implant density in the present study.…”
Section: Discussionsupporting
confidence: 90%
“…Chen J et al 19 in a retrospective review of 39 patients noted a positive correlation between implant density and curve correction. Sariylimaz & Ozkunt 20 in their comparative study and Tannous et al 21 in their retrospective study documented that curve correction in high versus low implant density had no significant correlation between Cobb angle correction and implant density. Our study had a few limitations such as the small number of patients and retrospective nature of our study design.…”
Section: Discussionmentioning
confidence: 92%
“…In all-screw constructs, literature describes different results on curve correction. Some find a significantly higher curve correction in high-density constructs, while other studies contradict this [21,24,[33][34][35][36][37][38][39][40]. This may be caused by the flexibility of the curves and screw position [38][39][40][41].…”
Section: Discussionmentioning
confidence: 99%